2015
DOI: 10.1073/pnas.1520333113
|View full text |Cite
|
Sign up to set email alerts
|

A cell wall damage response mediated by a sensor kinase/response regulator pair enables beta-lactam tolerance

Abstract: The bacterial cell wall is critical for maintenance of cell shape and survival. Following exposure to antibiotics that target enzymes required for cell wall synthesis, bacteria typically lyse. Although several cell envelope stress response systems have been well described, there is little knowledge of systems that modulate cell wall synthesis in response to cell wall damage, particularly in Gram-negative bacteria. Here we describe WigK/WigR, a histidine kinase/response regulator pair that enables Vibrio choler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
103
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 39 publications
12
103
0
2
Order By: Relevance
“…Our results demonstrated that deletion of vxrB did not impact motility but that overexpression of VxrB led to a decrease in motility. This is consistent with results from a previous study that demonstrated that overexpression of wild-type VxrB or constitutively active VxrB resulted in a loss of motility (36).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results demonstrated that deletion of vxrB did not impact motility but that overexpression of VxrB led to a decrease in motility. This is consistent with results from a previous study that demonstrated that overexpression of wild-type VxrB or constitutively active VxrB resulted in a loss of motility (36).…”
Section: Discussionsupporting
confidence: 93%
“…Another recent study additionally showed that the VxrAB TCS plays a role in cell wall homeostasis in response to antibiotic treatment (in that study, the authors renamed VxrAB as WigKR) (36). However, this is the first report of its role in the regulation of biofilm-gene expression.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Overexpression of V. cholerae ’s primary housekeeping endopeptidases, ShyA or ShyC (Dörr et al , ), was unable to appreciably reduce chaining in the ∆2 LTG mutant (Fig. A) (functional expression of these constructs was validated by their ability to complement a mutant defective in multiple endopeptidases [Dörr et al , ]). Similarly, overexpression of V. cholerae ’s only amidase, AmiB (co‐overexpressed with its activators NlpD and EnvC [Uehara et al , ; Yang et al , ; Möll et al , ]), demonstrated functionality by complementing the ∆ amiB mutant (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…pAM299 was conjugated into V. cholerae as a single crossover, without counterselection. For fluorescent localization or detection of proteins by western blot, genes were cloned into pBAD33 (Guzman et al , ) or pHL100 (Dörr, Alvarez, et al , ).…”
Section: Methodsmentioning
confidence: 99%